Cytotaxonomy of Simulium (Montisimulium) ghoomense (Diptera: Simuliidae) from the Darjeeling Hills, India - Henry, Willie; Thapa, Sachin; Adler, Peter H.; Dey, Subrata Kumar; Varma, Rakesh (Zootaxa, 2011)
The polytene chromosomes are mapped for a scarce Himalayan simuliid, Simulium (Montisimulium) ghoomense Datta, from the Darjeeling area of India. This species has three tightly paired polytene chromosomes with a haploid number of 3. Chromosomes I, II, and III account for 39.6%, 30.3%, and 30.1% of the total complement length, respectively. The centromeres of chromosomes II and III consistently form a putative partial chromocenter. Sex chromosomes are undifferentiated and polymorphisms and sibling species are lacking in a sample of 35 larvae. This is the first chromosomal map for a species in the subgenus Montisimulium in India.